Renovated structure within the Hanuman Garhi temple complex - Temples of India Project Team (Jio Institute, 2024)
This is a renovated structure, in which the sandstone pillars of the semi-open porch and the architrave of the garbhagriha of the temple are from the medieval period. The figure of Hanuman enshrined in the temple also belongs to the 12th century CE as per the inscription found on its pedestal. This temple complex gets its name from the life-size figure of Hanuman in the temple.